2023
DOI: 10.17755/esosder.1197849
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Psi̇koloji̇k Esnekli̇k Ölçeği̇’ Ni̇n Geli̇şti̇ri̇lmesi̇

Abstract: Bu çalışma, öğretmenlerin psikolojik esneklik düzeylerini belirleyebilmek için bir ölçme aracı geliştirmeyi amaçlamaktadır. Psikolojik esneklik, Kabul ve Kararlılık Kuramı’ nın temelidir ve kişinin şimdiki anda var olan duygu ve düşünceleriyle temasta olması ve kişinin kendisi için önemli olan değerleri doğrultusunda davranmasıdır. Öğretmelerin eğitim ortamlarındaki psikolojik esneklik düzeylerini belirlemeye yönelik bir ölçme aracı bulunmamaktadır. Bu amaçla geliştirilen Öğretmen Psikolojik Esneklik Ölçeği’ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…When the studies in the literature are examined, the attitude scale studies on learning German (Hanbay, 2008;Çelikkaya, 2013;Alyaz, 2011;Küçük, 2007;Üstün & Tanrıkulu 2021;Koç & Yastıbaş, 2022;Kırmızı, 2013;) attitude scale studies (Kara, 2010;Aydoğmuş, M. & Kurnaz, 2017;). However, no study has been found in the literature that focuses on all grade levels of secondary education and developed an attitude scale for secondary school students to learn German as a second foreign language.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…When the studies in the literature are examined, the attitude scale studies on learning German (Hanbay, 2008;Çelikkaya, 2013;Alyaz, 2011;Küçük, 2007;Üstün & Tanrıkulu 2021;Koç & Yastıbaş, 2022;Kırmızı, 2013;) attitude scale studies (Kara, 2010;Aydoğmuş, M. & Kurnaz, 2017;). However, no study has been found in the literature that focuses on all grade levels of secondary education and developed an attitude scale for secondary school students to learn German as a second foreign language.…”
Section: Findings and Discussionmentioning
confidence: 99%